Pendampingan Digitalisasi dan Penataan Arsip Keuangan sebagai Upaya Peningkatan Akuntabilitas Laporan Keuangan PMI Kota Malang - Zaenuddin Zaenuddin; Muhammad Syafiq; Syamsul Bahri; Endah Puspitosarie; Khojanah Hasan (Masyarakat Mandiri : Jurnal Pengabdian dan Pembangunan Lokal, 2026)
The Indonesian Red Cross (PMI) Malang City, as a humanitarian organization managing public funds, is required to produce financial reports that are accountable and transparent. However, preliminary observations revealed several challenges in financial records management, including the continued use of manual archiving systems, the absence of standardized document classification, and limited staff capacity in managing financial archives. These issues have the potential to hinder the preparation of financial statements, audit processes, and the retrieval of transaction records. This community service program aimed to enhance the capacity of PMI Malang City’s financial management staff through assistance in developing a more systematic and well-organized financial archiving system. The program adopted a participatory approach involving observation, Focus Group Discussions (FGDs), training, mentoring, and hands-on practice. The implementation consisted of four stages: preparation, mentoring activities, archiving system implementation, and program evaluation and sustainability. The results demonstrated significant improvements in the organization of financial documents, easier retrieval of transaction evidence, greater accuracy in financial reporting, and increased staff awareness of the importance of financial archiving in accordance with accountability principles. Overall, the program contributed to strengthening the financial governance of the humanitarian organization by establishing a more effective, systematic, and sustainable financial archiving system.